2018
DOI: 10.1089/vbz.2017.2146
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Control of NymphalIxodes scapularis: Effectiveness of White-Tailed Deer Reduction, the Entomopathogenic FungusMetarhizium anisopliae, and Fipronil-Based Rodent Bait Boxes

Abstract: Pathogens transmitted by ticks are the leading cause of arthropod-associated human diseases in the United States and managing the risk of exposure to potentially infected ticks is of vital public health importance. A 3-year integrated tick management program to control blacklegged ticks, Ixodes scapularis, the primary vector for the pathogenic agents of Lyme disease, human anaplasmosis, and babesiosis, was implemented in the town of Redding in southwestern Connecticut beginning in 2013. Combinations of white-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 51 publications
0
38
1
1
Order By: Relevance
“…Mathematical modeling and in field experiments done in the USA have shown that abundance of the North American tick Ixodes scapularis, a close relative of I. ricinus, is strongly associated with density of deer [84]. A decrease in numbers of deer was consistently associated with a decrease in tick population in following years [85,86]. Field studies in Europe yielded similar results for I. ricinus [87,88].…”
Section: Tick Host Managementmentioning
confidence: 78%
See 1 more Smart Citation
“…Mathematical modeling and in field experiments done in the USA have shown that abundance of the North American tick Ixodes scapularis, a close relative of I. ricinus, is strongly associated with density of deer [84]. A decrease in numbers of deer was consistently associated with a decrease in tick population in following years [85,86]. Field studies in Europe yielded similar results for I. ricinus [87,88].…”
Section: Tick Host Managementmentioning
confidence: 78%
“…Small vertebrates, especially rodents, are important reservoirs of most TBPs, which makes them potential targets for prophylactic approaches. In one such application of this strategy, placing of acaricide containing rodent bait boxes led to decrease in Lyme borreliosis prevalence USA [86]. Similarly, providing the rodents with acaricide-treated cotton for nest lining could lead to decrease in TBDs in treated areas [91].…”
Section: Tick Host Managementmentioning
confidence: 99%
“…A few integrated intervention approaches that combine two or three environmentally based control methods have been shown to effectively reduce abundance of host-seeking I. scapularis nymphs [26,27,119121], but none of these integrated approaches have yet been evaluated with the gold standard of human infection with an I. scapularis -borne pathogen as an outcome measure [28]. As suggested by the chain of events outlined in Figure 5, we also need to think outside the box and consider integrated intervention approaches that – rather than just combining two or more environmentally-based control methods – also include changes in human behavior and the use of existing personal protective measures.…”
Section: Controlling I Scapularis and Reducing Tick-borne Diseases Imentioning
confidence: 99%
“…All methodologies described were approved by the Connecticut Agricultural Experiment Station's IACUC (S02-17, S03-05, P22-14, P27-16) and the Wildlife Division of the Connecticut Department of Energy and Environmental Protection. From 2007-2019, extensive P. leucopus trapping occurred for investigations into the efficacy of various integrated tick management, reservoir-targeted vaccine, landscape management, and reservoir host research projects [25][26][27][28][29][30][31][32]. Trapping occurred in the towns of Guilford, Hampton, Litchfield, Lyme, Mansfield, Norfolk, North Branford, and Redding, CT. Limited P. leucopus trapping occurred from 2001-2004 in Cornwall, Groton, Old Lyme, Salisbury, Weston, and Westport with some deer mice captures (Peromyscus maniculatus Wagner) in Cornwall and Salisbury.…”
Section: Methodsmentioning
confidence: 99%